Spatiotemporal variations of vegetation and its determinants in the National Key Ecological Function Area on Loess Plateau between 2000 and 2015. Issue 10 (15th April 2019) - Hao, Haiguang; Li, Yuanyuan; Zhang, Huiyuan; Zhai, Ruixue; Liu, Haiyan
Abstract: China defined 25 National Key Ecological Function Areas in 2010 and adopted various measures to support ecosystem restoration in these areas. During the process of environment policymaking, it is important to observe the variation of vegetation and its driving factors. In this paper, we chose the National Key Ecological Function Area (NKEFA) on Loess Plateau as the study area. Based on MODIS‐NDVI data between 2000 and 2015, the trend analysis was used to depict the change in NDVI and the stepwise regression analysis method was used to quantitatively assess its determinants. The results show that: (a) The vegetation coverage in study area was low in the northwest and high in the southeast, corresponding to the distribution of precipitation and temperature. (b) NDVI in the growing season increased remarkably from 0.2841 in 2000 to 0.4199 in 2015 with a linear tendency of 0.085/10a. About 71.22% of the study area experienced an extremely significant increasing of NDVI, while only 0.03% of the total area suffered from significant decreasing of NDVI. (c) Compared to climatic factors, ecosystem conservation policies, and labor transfer contributed more to the vegetation changes in the study area. In order to ensure ecological security and sustainable development in these areas, it is necessary to maintain the continuity of ecological compensation policy. Moreover, developing targeted eco‐compensation policies and encouraging farmers to participate in nonfarm employment are effective ways to reach a win–win outcome of reducing the ecosystem pressure and improving the welfare of rural households. Abstract : NDVI in the National Key Ecological Function Area on Loess Plateau is low in the northwest and high in the southeast. From 2000 to 2015, the average NDVI in the study area increased by 47.8%, which was mainly influenced by ecosystem conservation policies and labor transfer.